Commodity Transport Studies Iron and Steel Part II Appendices - Planning Commission (Planning Commission, 1967)
Location-wise and category-wise demand for rolled mild steel for large and medium scale industries in 1970-71 (based on sanctioned capacities for Engineering Industries up to December 1965) State-wise and category-wise demand for rolled-mild steel for large and medium scale industries in 1970-71 (Based on known sanctioned capacities for Engineering Industries up to December 1965) Estimated requirement of various categories of rolled-mild steel for miscellaneous industries in 1970-71 (Based on known sanctioned capacities for Engineering Industries up to December 1965) Estimated requirement of various categories of rolled-mild steel for small scale industries Estimated requirement of steel for Industrial Maintenance for 1970-71 Estimated requirement of semis for steel forging units in 1970-71 Manufacture of wagons at Railway workshops during wagon building year 1963-64 Manufacture of wagons by Private Companies during the wagon building year 1963-64 Estimated requirement of rolled-mild steel category-wise for the manufacture of Railway wagons in 1970-71 Estimated requirement of Rolled Mild Steel category-wise for the manufacture of Railway coaches in 1970-71.
Joint Technical Group for Transport Planning, Planning Commission
Joint Technical Group for Transport Planning, Planning Commission